2009
DOI: 10.1007/s10103-009-0740-x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc phthalocyanine-loaded PLGA biodegradable nanoparticles for photodynamic therapy in tumor-bearing mice

Abstract: Nanoparticles formulated from the biodegradable copolymer poly(lactic-coglycolic acid) (PLGA) were investigated as a drug delivery system to enhance tissue uptake, permeation, and targeting of zinc(II) phthalocyanine (ZnPc) for photodynamic therapy. Three ZnPc nanoparticle formulations were prepared using a solvent emulsion evaporation method and the influence of sonication time on nanoparticle shape, encapsulation and size distribution, in vitro release, and in vivo photodynamic efficiency in tumor-bearing mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 42 publications
5
56
1
Order By: Relevance
“…When compared to high-dose administration of free Ce6 (2.5 mg/kg), low-dose administration of NP1 NPs (equivalent Ce6 0.5 mg/kg body) were found to be more efficient for tumor regression . Also our results coincide with the results obtained by Fadel et al (2010).…”
Section: Macroscopic Analysis and Histological Studies Of Paraffin Sesupporting
confidence: 93%
See 2 more Smart Citations
“…When compared to high-dose administration of free Ce6 (2.5 mg/kg), low-dose administration of NP1 NPs (equivalent Ce6 0.5 mg/kg body) were found to be more efficient for tumor regression . Also our results coincide with the results obtained by Fadel et al (2010).…”
Section: Macroscopic Analysis and Histological Studies Of Paraffin Sesupporting
confidence: 93%
“…7b. These results are in accordance with the results obtained by Lee et al (2012) and Fadel et al (2010). They formulated nanoparticles from the biodegradable copolymer poly (lactic-co glycolic acid) (PLGA) for targeting of zinc (II) phthalocyanine (ZnPc) for PDT in Ehrlich ascites carcinoma bearing mice.…”
Section: Tumor Growth and Growth Ratesupporting
confidence: 90%
See 1 more Smart Citation
“…Zinc phthalocyanine (ZnPc) is an organic semiconductor compound (Eley 1948), which is used as a photosensitizer for Photodynamic therapy (PDT) (Fadel et al 2010;Ping et al 2016); and in optoelectronic applications such as organic light-emitting diodes (OLED) (Run-Da et al 2013;Heo et al 2013) and organic photovoltaics (OPVs) (Kim and Bard 2004). The size effect on the electrical and optical properties of metal-free phthalocyanine nanoparticles have been studied using the physical method such as mechanical grinding, it's found that as the material's size gets smaller their photoconductivity efficiency was improved (Saito et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the photosensitizer acts as an energy transducer and transfers energy to molecular oxygen, resulting in the production of many reactive oxygen species (ROS), such as singlet oxygen ( 1 O2), hydrogen peroxide(H2O2), and superoxide radicals (O2-). Singlet oxygen ( 1 O2) is a predominant cytotoxic agent in PDT [14][15][16].…”
Section: Introductionmentioning
confidence: 99%